ETHNOGRAPHY OF COMMUNICATION: THE WAY OF SPEAKING IN BANJAR COMMUNITY OF SOUTH KALIMANTAN - Rafiqoh, Putri Ayu Hadayatur (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2025)
The concept of ethnography of communication examines the communication patterns of the Banjar community, including the use of language, speech norms, and the social context that surrounds it. This study comprehensively describes how the Banjar community interprets and practices communication in everyday life, as well as cultural actions in the form of events expressed by the community through language. The relevance between language and ethnography is seen in the cultural expression explained through language events. This paper explains the ethnography of the Banjar language based on Hymes' theory. Based on the results of the study, it was found that their speech manners show high respect for the values of politeness, customs, and Islamic teachings as the main guide in communicating. The geographical conditions of the Banjar ethnic group, which is located in a river environment, is also a factor in the large number of special vocabularies related to river life that are only owned and interpreted by the community. The Banjar language has variations in the level of refinement used according to social status, age, or closeness of the relationship between the speaker and the listener, reflecting an attitude of mutual respect in social interaction. In addition, deliberation is the main means of decision-making, while conflict resolution is carried out by prioritizing family dialogue, customary law, and religious values. Keywords: ethnography of communication, Banjar community, speaking